PENGARUH MEDIA SOSIAL TERHADAP KESEHATAN MENTAL PADA REMAJA - Aisyah Fitriah; Dzaky Juliansyah; Umi Salamah; M Anugrah Utama; Opie Karunia Falah; Aseh Miati (CV. Doki Course and Training, 2023)
Adolescent mental health affected by social media is a topic that has been much debated in recent years. The high use of social media makes these channels an important element in the process of adolescent development. Social media is often considered to have a negative impact on adolescents. The use of social media is considered to have a risk for adolescent psychosocial deviations, such as self-esteem, ideal body image, and adolescent identity. In addition, social media is also related to issues regarding cyberbullying, easier access to pornography, and sexting behavior or exchanging messages of a sexual nature. This study uses a quantitative research approach with respect to numerical or numerical data. This study aims to find out and reveal whether there is a relationship or not and to find out how much influence there is between two variables, namely the use of social media and the mental health of social media users in Indonesia. And the results in this study are the results of the gender comparison test in social media research where men are more dominant in using social media than women, and the results of mental health are women who are more dominant in feeling mental health or mental health than men. the results of the comparative test in the study of the influence of social media on the mental health of adolescents with a comparison test according to age are 21-25 years old, who are equally dominant in using social media and experiencing mental health compared to other ages.